Implementasi Metode Kombinasi SAW-TOPSIS Untuk Pengambilan Keputusan Penerima Bantuan Program Keluarga Harapan: Implementation Of The SAW-TOPSIS Combination Method For Decision-Making For Family Hope Program Assistance Recipients - Sitepu, Lulu Agatha Br; Astawa, I Wayan Puja; Sukajaya, I.N. (DAS Institute, 2025)
The Family Hope Program is a conditional social assistance program from the Indonesian government designed to help poor and vulnerable families. However, in its implementation, problems related to the accuracy of targeting aid recipients are still often encountered, so a systematic approach using a multi-criteria decision-making method is needed for the selection of aid recipients. This study aims to apply and assess the level of accuracy of combining two methods in decision-making, namely Simple Additive Weighting (SAW) and Technique for Order Preference by Similarity to Ideal Solution (TOPSIS), in the process of distributing PKH assistance so that the distribution of aid is more on target. The research was conducted using secondary data from the Integrated Social Welfare Data (DTKS) of Sukanalu Village, Karo Regency, North Sumatra in 2024/2025, as well as primary data from field observations. Eight criteria were used in the selection process, namely the existence of pregnant/lactating women, toddlers, school children, the elderly, people with disabilities, employment, receipt of other assistance, and the number of dependents. The results of the implementation show that the SAW-TOPSIS method can provide an objective ranking of aid recipients. Evaluation using confusion matrix resulted in an accuracy of 82.9%, precision of 82.6%, and recall of 91,3%. This value shows that the SAW-TOPSIS combination method is effective in improving the accuracy of determining PKH aid recipients and can be a basis for village governments in distributing aid fairly and efficiently.